Silica Gel Powder Catalyzed Stereoselective Conversion of 2-(2-acetylphenoxy)-3- (triphenylphosphoranylidene)- butanedioates to Dialkyl (Z)-2-(2-Acetylphenoxy)- 2- butenedioates in Solvent-free Conditions - Ramazani, Ali; Rahimifard, Mahshid; Souldozi, Ali (Asian Journal of Chemistry, 2010)
Protonation of the highly reactive 1 : 1 intermediates, produced in the reaction between triphenylphosphine and dialkyl acetylenedicarboxylates, by 1-(2-hydroxyphenyl)-1-ethanone leads to vinyltriphenylphosphonium salts, which undergo Michael addition reaction with conjugate base to produce dialkyl 2-(2-acetylphenoxy)-3-(triphenylphosphoranylidene) butanedioates. Silica gel powder was found to catalyze stereoselective conversion of dialkyl 2-(2-acetylphenoxy)-3-(triphenylphosphoranylidene)butanedioates to dialkyl (Z)-2-(2-acetylphenoxy)-2-butenedioates in solvent-free conditions at 100ºC.